5+3x=7(x+3)
Answer:
-4
Step-by-step explanation:
Simplifying
5 + 3x = 7(x + 3)
Reorder the terms:
5 + 3x = 7(3 + x)
5 + 3x = (3 * 7 + x * 7)
5 + 3x = (21 + 7x)
Solving
5 + 3x = 21 + 7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7x' to each side of the equation.
5 + 3x + -7x = 21 + 7x + -7x
Combine like terms: 3x + -7x = -4x
5 + -4x = 21 + 7x + -7x
Combine like terms: 7x + -7x = 0
5 + -4x = 21 + 0
5 + -4x = 21
Add '-5' to each side of the equation.
5 + -5 + -4x = 21 + -5
Combine like terms: 5 + -5 = 0
0 + -4x = 21 + -5
-4x = 21 + -5
Combine like terms: 21 + -5 = 16
-4x = 16
Divide each side by '-4'.
x = -4
Simplifying
x = -4
(-0.75x+6)-(2.5x-1.9)
Answer:
Its translation C.
Step-by-step explanation:
And to give someone brainliest 2 people have to answer and then you give brainliest to whoever was the most helpful :)